Evaluation of steel corrosion in cement mortars containing catalytic cracking catalyst residue (FCC) (2013)
In this article, the performance to the corrosion of cement mortars added with a petrochemical industry waste, in environments contaminated with chlorides (sodium chloride, NaCl 3.5%) and/or carbonic anhydride, CO2(3% CO2, 65% RH and 25 ° C), is analyzed. A waste, named catalyst catalytic cracking residue (FCC), from a refinery Colombian was used. This material has a high content of silica and alumina, partially amorphous morphology and a high reactivity. For the study, were prepared mortars from cement ordinary Portland with 12% of FCC as cement replacement, both simple and reinforced. The potential and corrosion current were evaluated. Additionally, in the unreinforced specimens, it was determined the total absorption, penetration of chlorides, carbonation front and resistivity. From the results, it concludes that the addition of FCC in mortars has a positive effect on the performance of these materials against the attack of chlorides and CO2, specifically a reduction of around 50% in chloride permeabilityand penetration CO2, and a 128% increase in the resistivity of the mortar. The corrosion values reported by blended mortars are lower than the reference sample, especially in presence of chlorides.